2021
DOI: 10.3390/biomedicines9121757
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin as a Biomarker of Cardiovascular Diseases: A Clinical Perspective

Abstract: Accounting for almost one-third of the global mortality, cardiovascular diseases (CVDs) represent a major global health issue. Emerging data suggest that most of the well-established mechanistic explanations regarding the cardiovascular pathophysiology are flawed, and cannot fully explain the progression and long-term effects of these diseases. On the other hand, dysregulation of the sympathetic nervous system (SNS) has emerged as an important player in the pathophysiology of CVDs. Even though upregulated SNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 82 publications
0
13
0
4
Order By: Relevance
“…Concerning the central nervous system, Cts plays an important role in cardiorespiratory control ( 14 ). Gaede et al showed that Cts antagonizes both nAChR and β-adrenergic receptors involved in cardiovascular regulation using urethane-anesthetized, vagotomized rats.…”
Section: Catestatin and Regulation Of Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the central nervous system, Cts plays an important role in cardiorespiratory control ( 14 ). Gaede et al showed that Cts antagonizes both nAChR and β-adrenergic receptors involved in cardiovascular regulation using urethane-anesthetized, vagotomized rats.…”
Section: Catestatin and Regulation Of Blood Pressurementioning
confidence: 99%
“…Further studies showed that Cts inhibits CA release also due to adenylate cyclase-activating polypeptide stimulation and regulates dense core vesicle quanta ( 13 ) ( Figure 1 ). Moreover, Cts has emerged as a pleiotropic peptide, which – among others – is involved in the regulation of the cardiovascular and immune system, as well as metabolic homeostasis ( 14 , 17 , 25 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these mechanisms have deleterious effects on cardiac structure and performance, leading not only to symptomatic HF, but also to HF decompensations. In addition, higher levels of plasma circulating NA seen from Stage B in HF, were strongly linked to a worsening of systolic dysfunction and a progression of interstitial fluid accumulation, marking the onset of edema formation at biochemical/molecular level (26)(27)(28)(29)(30).…”
Section: Biomarkers Of Sympathetic Activationmentioning
confidence: 99%
“…Specifically, CgA demonstrated to be a powerful predictive marker of mortality and morbidity in HF subjects (28). It inhibits cardiac remodeling, reduce arterial blood pressure and decrease endothelial and vascular inflammation (24,28,29). The last two mentioned effects may suggest its involvement in body fluid homeostasis, thus an increased circulating plasma level of CgA observed in HF patients, would translate as a compensatory mechanism meant to limit acute/chronic fluid overload.…”
Section: Biomarkers Of Sympathetic Activationmentioning
confidence: 99%